Heat Transfer in an Upper Convected Maxwell Fluid with Fluid Particle Suspension (Advances in Applied Mathematics and Mechanics, 2018)
An analysis is carried out to study the magnetohydrodynamic (MHD) flowand heat transfer characteristics of an electrically conducting dusty non-Newtonianfluid, namely, the upper convected Maxwell (UCM) fluid over a stretching sheet. Thestretching velocity and the temperature at the surface are assumed to vary linearly withthe distance from the origin. Using a similarity transformation, the governing nonlinearpartial differential equations of the model problem are transformed into couplednon-linear ordinary differential equations and the equations are solved numericallyby a second order finite difference implicit method known as the Keller-box method.Comparisons with the available results in the literature are presented as a special case.The effects of the physical parameters on the fluid velocity, the velocity of the dustparticle, the density of the dust particle, the fluid temperature, the dust-phase temperature,the skin friction, and the wall-temperature gradient are presented throughtables and graphs. It is observed that, Maxwell fluid reduces the wall-shear stress. Also,the fluid particle interaction reduces the fluid temperature in the boundary layer.Furthermore, the results obtained for the flow and heat transfer characteristics revealmany interesting behaviors that warrant further study on the non-Newtonian fluidflow phenomena, especially the dusty UCM fluid flow phenomena.